Особливості проростання насіння й ріст сходів видів Betula L. у сім’ядольній фазі - Parkhomenko, L.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
Resultats of seed germination and seedling develop ment of birches investigation at cotyledonary stage are given. Morphological parameters, form and color of hypocotyls and cotyledons of 25 species and two forms of Betula are presented.